Quadrupedal robot with tendon-driven origami legs - Kim, Jinho; Im, Euncheol; Lee, Yisoo; Cha, Youngsu (Elsevier BV, 2024)
In this study, a novel quadrupedal robot with origami cylinders for locomotion is proposed. The proposed robot used a bounding gait, and tendon-driven Kresling-patterned origami cylinders as legs. The origami cylinder actuators were controlled by using a predefined signal with conditions determined through series of experiments. The robot moved at locomotion speed of 47.51 mm/s, which is about 0.283 body length per second. Specifically, the locomotion of the robot was analyzed by dividing the gait into multiple phases. During the phases, a dynamics model was developed to describe the motion of the robot. In addition, we observed that the dynamics model's result was in accordance with the experimental result.